[PP.16.18] ASSOCIATION BETWEEN HYPERURICEMIA AND ABNORMAL HEART RATE RECOVERY IN HYPERTENSIVE PATIENTS WITH NON-DIPPING PATTERN. (September 2016) - Predotti, P.; Giallauria, F.; Viggiani, A.; Citro, R.; Ravera, A.; Casciello, A.; Maggio, M.; Ciardo, M.; Cittadini, A.; Vigorito, C.
Abstract : Objective: Sympatho-vagal balance, as measured by heart rate recovery (HRR) at the first minute after exercise, is correlated with long-term prognosis in patients with cardiovascular disease. Higher serum uric acid (UA) is an independent risk factor for hypertension; and hyperuricemia is associated with non-dipping pattern (<10% fall in nocturnal blood pressure) among hypertensive patients. Given the importance of nondipper hypertension on cardiovascular outcomes, the present study tested the hypothesis that heart rate recovery is associated with hyperuricemia among hypertensive patients with non-dipping pattern. Design and method: The study included 122 essential hypertensive patients (64% Male, 55 ± 3 years) subdivided into two groups according to 24-hour ABPM resuts: 48 dippers and 74 nondippers. All patients underwent ambulatory blood pressure monitoring and exercise stress testing. HRR was calculated as the difference between the heart rate at peak exercise and after 1-min cooling down. Results: No significant differences in office blood pressure (BP) values were observed between non-dipper and dipper hypertensive patients (Figure 1-2). Compared to dippers, the nocturnal systolic (Figure 3), diastolic (Figure 4), and mean BP levels (Figure 5), were found to be significantly greater among non-dippers, respectively. Non-dippers hypertensive patients showed significantly higher serum UA levels compared to dippers (Figure 6); and high sensitivity C-reactive protein (hsCRP) (Figure 7). Non-dippers hypertensive patients showed significantly lower HRR compared to dippers (Figure 8). Figure. No caption available. Among non-dippers, a significant correlation between UA levels and HRR was observed (r = 0.38, P < 0.001). After adjusting for age, gender, body mass index, smoking habits, creatinine levels, hsCRP and comorbidity, multivariate analysis revealed an independent association between HRR and serum UA levels among non-dippers (ß = 0.312, P = 0.002). Conclusions: Serum UA is independently associated with abnormal heart rate recovery in hypertensive patients with nondipper circadian pattern.